Temple compound of Harsha Bhairon on Harsha Hill - Temples of India Project Team (Jio Institute, 2024)
The shrine of Harsha Bhairon is now an epicentre of spiritual activities at Harsha Hill. This late medieval structure has an enclosure wall, upon which sculptures are affixed both inside and outside.